The Role of the Bone Strength on the Cyst Growth in the Mandible - MIODOWSKA, Justyna; BIELSKI, Jan; KROMKA-SZYDEK, Magdalena (Engineering Transactions, 2019)
Intracystic fluid pressure is discussed as a potentially important factor influencing a bone cyst growth. This process can develop in the course of months. However, the exact mechanism remains speculative. In this paper, we use an established mathematical model to evaluate whether the presence of pressurized fluid in bone cavities may result in cyst growth. A continuous function of bone density rate vs. mechanical stimulus is used. The numerical model of the mandible with the cyst is used to predict the stress-stimulated change in bone density around the cavity.